METHODS FOR PROMOTING INNOVATION IN THE UNIVERSITY INDUSTRIAL DESIGN STUDIO - Florin CIOFU (Fiabilitate şi Durabilitate)
Flexible and original thinking is the key to outstanding design. In order to teach design effectively we must therefore offer students a framework that isn’t restrictive and allows them room to develop their own individual design process. This doesn’t mean that we can’t offer our students technicaladvice or suggestions that might influence their process. Creativity blossoms and a student’s creative process is discovered when the individual is immersed in an environment conducive to innovative thinking. Promoting mentally active drawing, encouraging students to identify user problems, perform in-depth research, and make discoveries through hands-on model-making are some of the areas elaborated upon in this paper.